Sectoral projection of manpower needs in Malaysia / Kamal Salih - Salih, Kamal (1992)
One of the major challenges in the 1990s is to shift the focus of policy making from economic growth and employment generation to human resource development (HRD). HRD is at the moment most widely discussed in both international and national meetings. Lucas and Verry (1989), in their discussion on human resource led development and labour options for Malaysia, highlighted that human resource accumulation presumably shifts the Malaysian economy's comparative advantage towards human resource intensive products just as physical capital investment would shift an economy to more capital intensity. The conventional approach to employment strategies in this region has been to promote rapid economic growth in production lines which can productively absorb a lot of labour. The labour absorption strategy is based on utilising unskilled workers which undoubtedly leads to employment creation, but it is vulnerable to technology and organisation change's. In addition, it is also sensitive to changes in relative wage levels. The difference in the human resource-driven strategy is the competitive edge of the economy, neither the commodities nor the cheap labour, but skills, entrepreneurship and research. What has happened in the first tier of the NIEs in Asia - in Korea, Singapore and Hong Kong - is that those economies have shifted from labour-based lines of production to more skills and entrepreneurship-intensive technologies (Edgren, 1990). The extent to which they can be called HRD-driven strategies varies, but it is quite clear that the shift towards skills and innovation is one of the explanations why the second line of flying geese has continued to move so fast inspite of emerging labour shortages and rising wage levels, such as in the case of Malaysia. The proof of the HRD-based development strategy is that the structural transformation of the economy is facilitated by arising quality of labour supply, and not primarily by overseas demand factors.